Impaired cortical mitochondrial function following TBI precedes behavioral changes - Watson, William D.; Buonora, John; Yarnell, Angela; Lucky, Jessica J.; D'Acchille, Michaela I.; McMullen, David C.; Boston, Andrew G.; Kuczmarski, Andrew V.; Kean, William S.; Verma, Ajay; Grunberg, Neil E.; Cole, Jeffrey T. (Frontiers in Neuroenergetics, 2014)
Traumatic brain injury (TBI) pathophysiology can be attributed to either the immediate, primary physical injury or the delayed, secondary injury which begins minutes to hours after the initial injury and can persist for several months or longer. Because these secondary cascades are delayed and last for a significant time period post TBI, they are primary research targets for new therapeutics. To investigate changes in mitochondrial function after a brain injury, both the cortical impact site and ipsilateral hippocampus of adult male rats 7 and 17 days after a controlled cortical impact (CCI) injury were examined. State 3, state 4 and uncoupler-stimulated rates of oxygen consumption, respiratory control ratios were measured and membrane potential quantified, and all were significantly decreased in 7 day post-TBI cortical mitochondria. By contrast, hippocampal mitochondria at 7 days showed only nonsignificant decreases in rates of oxygen consumption and membrane potential. NADH oxidase activities measured in disrupted mitochondria were normal in both injured cortex and hippocampus at 7 days post-CCI. Respiratory and phosphorylation capacities at 17 days post-CCI were comparable to naïve animals for both cortical and hippocampus mitochondria. However, unlike oxidative phosphorylation, membrane potential of mitochondria in the cortical lining of the impact site did not recover at 17 days, suggesting that while diminished cortical membrane potential at 17 days does not adversely affect mitochondrial capacity to synthesize ATP, it may negatively impact other membrane potential-sensitive mitochondrial functions. Memory status, as assessed by a passive avoidance paradim, was not significantly impaired until 17 days after injury. These results indicate pronounced disturbances in cortical mitochondrial function 7 days after CCI which precede the behavioral impairment observed at 17 days.